2020
DOI: 10.1002/srin.202000448
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Transform and Specific Heat Capacity Characterization of Blast Furnace Slag with High Al2O3 in Heating Process

Abstract: The specific heat capacity (Cp) of blast furnace (BF) slag critically impacts BF smelting and reports on the Cp of BF slag with high Al2O3 are rare. Mineral transform and Cp characterization of synthesized BF slag (CaO–SiO2–MgO–Al2O3) with high Al2O3 in the heating process are herein discussed. Differential scanning calorimetry curves show a major exothermic peak at a low temperature and multiple endothermic peaks at elevated temperatures. The exothermic peak at approximately 920 °C appears when amorphous SiO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As shown in Figure 6, when the MgO/Al 2 O 3 ratio of the slag changed from 0.55 to 0.75, the end of the [SiO 4 ] 4− axisymmetric vibration band gradually expanded to the low wave number region, moving from 780 cm −1 to 760 cm −1 . It showed that the expansion of the [SiO 4 ] 4− axisymmetric vibration band reflected the increase in the distance between Si and O in the slag system [21][22][23][24], which meant that the degree of polymerization of the slag network structure decreased with the MgO/Al 2 O 3 ratio of slag. The groove center of the Si-O-Al bending vibration section gradually shifted to the right with the increase of the MgO/Al 2 O 3 ratio, and the strength gradually weakened, indicating that the Si-O-Al structure in the slag decreased.…”
Section: The Influence Of Mgo/al 2 O 3 Ratio and Basicity On The Thermal Stability Of Blast Furnace Slagmentioning
confidence: 99%
“…As shown in Figure 6, when the MgO/Al 2 O 3 ratio of the slag changed from 0.55 to 0.75, the end of the [SiO 4 ] 4− axisymmetric vibration band gradually expanded to the low wave number region, moving from 780 cm −1 to 760 cm −1 . It showed that the expansion of the [SiO 4 ] 4− axisymmetric vibration band reflected the increase in the distance between Si and O in the slag system [21][22][23][24], which meant that the degree of polymerization of the slag network structure decreased with the MgO/Al 2 O 3 ratio of slag. The groove center of the Si-O-Al bending vibration section gradually shifted to the right with the increase of the MgO/Al 2 O 3 ratio, and the strength gradually weakened, indicating that the Si-O-Al structure in the slag decreased.…”
Section: The Influence Of Mgo/al 2 O 3 Ratio and Basicity On The Thermal Stability Of Blast Furnace Slagmentioning
confidence: 99%
“…Australian ores have a high Al 2 O 3 content (w(Al 2 O 3 )), which results in a high w(Al 2 O 3 ) in the blast furnace smelting process [3][4][5][6][7][8][9][10][11][12]. The operation of the blast furnace is impacted, and the quality of the hot metal is reduced due to the high w(Al 2 O 3 ) content in the smelting process [13,14]. In addition, the energy used by China's steel industry was shown to constitute approximately 11% of the country's total energy consumption, and the energy used by the blast furnace smelting process constituted approximately 59% of that total by 2022.…”
Section: Introductionmentioning
confidence: 99%